2015
DOI: 10.1103/physrevlett.114.038301
|View full text |Cite
|
Sign up to set email alerts
|

Critical Casimir Forces and Colloidal Phase Transitions in a Near-Critical Solvent: A Simple Model Reveals a Rich Phase Diagram

Abstract: From experimental studies, it is well known that colloidal particles suspended in a near-critical binary solvent exhibit interesting aggregation phenomena, often associated with colloidal phase transitions and assumed to be driven by long-ranged solvent-mediated (SM) interactions (critical Casimir forces), set by the (diverging) correlation length of the solvent. We present the first simulation and theoretical study of an explicit model of a ternary mixture that mimics this situation. Both the effective SM pai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(88 citation statements)
references
References 32 publications
5
83
0
Order By: Relevance
“…19,21 The coexistence curves of the three-dimensional system are broader, mainly due to the fact that the particle surface is proportional to R 2 as opposed to R in 2D; the colloidal particles in 3D are overall adsorbing more strongly for the same value of α. The phase diagrams also exhibit the same trends when decreasing the temperature, τ; the two-phase G-L(X) coexistence region broadens, and the critical point of the ternary system shifts towards the critical point of the pure solvent reservoir.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19,21 The coexistence curves of the three-dimensional system are broader, mainly due to the fact that the particle surface is proportional to R 2 as opposed to R in 2D; the colloidal particles in 3D are overall adsorbing more strongly for the same value of α. The phase diagrams also exhibit the same trends when decreasing the temperature, τ; the two-phase G-L(X) coexistence region broadens, and the critical point of the ternary system shifts towards the critical point of the pure solvent reservoir.…”
Section: Resultsmentioning
confidence: 99%
“…We do this by assessing the phase behavior and compare the overall topology of the resulting 3D phase diagram with that of a two-dimensional system. 19,21 This comparison is achieved by calculating the solvent chemical potential difference, ∆µ s , vs colloid packing fraction, η, phase diagrams of the ternary mixture at different reduced temperatures, τ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al 21 furthermore observed liquid, fcc crystal, and glass phases of the aggregated particles also for ℓ ∼ a ≫ ξ. We mention a number of theoretical papers on this near-critical aggregation [23][24][25][26][27][28][29][30] . In non-critical solvents, on the other hand, the particles often stick and form fractal aggregates due to the attractive van der Waals interaction 31 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent theories 28,29 , the colloidal particles were assumed to form one-component systems interacting via an attractive solvent-mediated interaction potential (∝ e −r/ξ ) and a repulsive electrostatic potential, where the particle separation r is smaller than ξ in aggregation. Very recently, Edison et al 30 has examined phase behavior of a three-component model on a 2D lattice to obtain aggregation of the third component.…”
Section: Introductionmentioning
confidence: 99%